Do Personality Features Influence Our Intuitions of the Mind-Body Problem? A Pilot Study - Havlík, Marek; Mladá, Karolína; Fajnerová, Iveta; Horáček, Jiří (Frontiers in Psychology, 2018)
The elusive relationship between the mental domain and the physical brain, known as the mind-body problem, is still a hot topic of discussion among philosophers and neuroscientists. Rather than solving this problem, our pilot study addresses the question as to whether personality features could influence intuitions of the mind-body problem, or more precisely, whether it is possible to identify a person’s intuitive inclinations towards dualism or materialism and their inclinations towards reduction of the mind to the brain. For the purposes of this pilot study, we developed a questionnaire, which employed several theories of analytic philosophy of the mind, in order to determine which category the participants would belong to. These main categories were dualism, non-reductive materialism and reductive materialism. To test whether personality features affect preferences for these categories, the participants were investigated by Cloninger’s Temperament and Character Inventory. We found significant differences in the self-transcendence dimension of the Temperament and Character Inventory between participants who were evaluated as dualists and those who were assessed as reductive materialists. Our data show that the personality dimension of self-transcendence correlates with intuitive inclination towards reductive materialism or dualism. In addition, our results suggest that ideas, theories and hypothetical solutions of the mind-body problem and possibly even conclusions, acceptance and disputations of thought experiments of philosophy of the mind, can be biased by personality traits. This fact should be taken into account in future discussions of the philosophy of the mind and may also be important for empirical research and an empirical understanding of the mind.